2013
DOI: 10.1152/jn.00809.2012
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine reduces NMDAR desensitization and differentially modulates peak amplitude of NMDAR currents, depending on GluN2 subunit composition

Abstract: Bolton AD, Phillips MA, Constantine-Paton M. Homocysteine reduces NMDAR desensitization and differentially modulates peak amplitude of NMDAR currents, depending on GluN2 subunit composition. J Neurophysiol 110: 1567-1582, 2013. First published July 17, 2013 doi:10.1152/jn.00809.2012.-N-methyl-D-aspartate receptors (NMDARs) have been linked to schizophrenia because agents that bind the receptor, like ketamine and phencyclidine, are capable of inducing schizophrenia-like symptoms. Here we show that the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 78 publications
2
21
0
Order By: Relevance
“…Several studies reported that HCY (Lipton et al, 1997; Ganapathy et al, 2011; Bolton et al, 2013), as well as its derivative, homocysteic acid, studied earlier (Provini et al, 1991; Kilić et al, 1992) is an agonist operating via the glutamate binding sites of the NMDARs. In addition, HCY at relatively high concentrations (above 1 mM HCY) can compete with glycine for the NMDAR co-agonist binding sites (Lipton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported that HCY (Lipton et al, 1997; Ganapathy et al, 2011; Bolton et al, 2013), as well as its derivative, homocysteic acid, studied earlier (Provini et al, 1991; Kilić et al, 1992) is an agonist operating via the glutamate binding sites of the NMDARs. In addition, HCY at relatively high concentrations (above 1 mM HCY) can compete with glycine for the NMDAR co-agonist binding sites (Lipton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HCY at relatively high concentrations (above 1 mM HCY) can compete with glycine for the NMDAR co-agonist binding sites (Lipton et al, 1997). Recently, effects of HCY at relatively high concentrations (up to 1 mM) on NMDA and glutamate activated currents transferred through the channels of recombinant NMDARs composed of the GluN1 and GluN2A, GluN1 and GluN2B or GluN1 and GluN2D subunits were studied (Bolton et al, 2013). It has been demonstrated, that HCY can differently modulate peak amplitude of currents activated by NMDA and glutamate and reduce NMDAR desensitization caused by NMDA and glutamate depending on GluN2 subunit compositions (Bolton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although management of diet and lifestyle is not sufficient of itself to control schizophrenia, nevertheless, attention to these aspects may optimize brain function, improve quality of life and reduce excess mortality [1, 2] commonly associated with schizophrenia. Efficacy of exercise in schizophrenia is supported by randomized, controlled clinical trials [3]Exercise-induced increases in hippocampal volume in schizophrenia are linked to improved short-term memory [4]Genetically based disturbances in folate metabolism may also be linked to negative symptoms [5], age of onset [6], and risk for weight gain [7]; metabolic syndrome [8]Elevated homocysteine levels [9, 10] may increase oxidative stress [11] and lead to inhibition of NMDAR-mediated neurotransmission [12]Genetic dysregulation of glutathione synthesis may also lead to increased brain oxidative stress [13]Treatment with folic acid + vitamin B12 may lead to improved negative symptoms in individuals with genetic alterations in folate absorption [14, 15] …”
Section: Diet and Lifestylementioning
confidence: 99%
“…Elevated homocysteine levels [9, 10] may increase oxidative stress [11] and lead to inhibition of NMDAR-mediated neurotransmission [12]…”
Section: Diet and Lifestylementioning
confidence: 99%